Potential of algal metabolites for the development of broad‐spectrum antiviral therapeutics: Possible implications in COVID‐19 therapy. (18th November 2020) - Sangtani, Rimjhim; Ghosh, Atreyee; Jha, Hem C.; Parmar, Hamendra Singh; Bala, Kiran
Abstract : Covid‐19 pandemic severely affected human health worldwide. Till October 19, 2020, total confirmed patients of COVID‐19 are 39, 944, 882, whereas 1, 111, 998 people died across the globe. Till to date, we do not have any specific medicine and/or vaccine to treat COVID‐19; however, research is still going on at war footing. So far vaccine development is concerned, here it is noteworthy that till now three major variants (named A, B, and C) of severe acute respiratory syndrome‐coronavirus2 (SARS‐CoV‐2) have been recognized. Increased mutational rate and formation of new viral variants may increase the attrition rate of vaccines and/or candidate chemotherapies. Herbal remedies are chemical cocktails, thus open another avenue for effective antiviral therapeutics development. In fact, India is a large country, which is densely populated, but the overall severity of COVID‐19 per million populations is lesser than any other country of the world. One of the major reasons for the aforesaid difference is the use of herbal remedies by the Government of India as a preventive measure for COVID‐19. Therefore, the present review focuses on the epidemiology and molecular pathogenesis of COVID‐19 and explores algal metabolites for their antiviral properties.